Differential ultracentrifugation coupled to small‐angle X‐ray scattering on macromolecular complexes. (1st June 2015) - Hynson, Robert M. G.; Duff, Anthony P.; Kirby, Nigel; Mudie, Stephan; Lee, Lawrence K.
<x xml:space="preserve">Abstract</x> Small‐angle X‐ray scattering (SAXS) can provide accurate structural information and low‐resolution shapes of macromolecules in solution. The technique is particularly amenable to large protein assemblies, which produce a strong scattering signal. Hence, SAXS can be a powerful tool to elucidate quaternary structure, especially when used in combination with high‐resolution structural techniques such as X‐ray crystallography and NMR. Sample requirements for SAXS experiments are stringent and only monodispersed samples can be satisfactorily analysed. Often, it is not possible to obtain a stable monodispersed sample of the protein of interest, in particular for multi‐subunit protein complexes. In these circumstances, when the complex is less than approximately 1 MDa, size exclusion chromatography (SEC) coupled with SAXS (SEC‐SAXS) can facilitate the separation of monodispersed protein from a polydispersed sample for a sufficient amount of time to collect useful SAXS data. However, many very large multi‐subunit macromolecular assemblies have not been successfully purified with SEC, and hence despite being well suited to SAXS there is often no way to produce sample of sufficient quality. Rather than SEC, differential ultracentrifugation (DU) is the method of choice for the final step in the purification of large macromolecular protein complexes. Here, a new method is described for collecting SAXS data on samples directly from the fractionated elution of ultracentrifuge tubes after DU. It is demonstrated using apoferritin as a model protein that, like SEC‐SAXS, DU‐coupled SAXS can facilitate simultaneous purification and data collection. It is envisaged that this new method will enable high‐quality SAXS data to be collected on a host of large macromolecular protein complex assemblies for the first time.